Maaf, Terima Kasih, Tolong Dan Permisi: Empat Kata Ajaib Dalam Pembentukan Karakter Sosial Anak - Nuraly Masum Aprily; Anfa Kamilatul Rosidah; Hani Hashipah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2023)
In an effort to form a quality generation, character education must be carried out from an early age. This article will describe the four magic words in the formation of children’s character in social life. This article was created to be a guide in everyday life and educated children to behave in social life in accordance with the values of correct behavior. This article uses research methods based on library research. Data collection techniques carried out ini research 1) reading, 2) taking notes, 3) processing research materials in achieving relevant results. Collection of primary data in this study from 17 articles and 1 book. The results of this study: First, the habit of using the word ”Sorry” is done through the guidance of parents or eduators. Second, the habit of saying the word ”thank you” is done by giving examples of activities for children to always say the word thank you. Third, the habituation of using the word ”please” is carried out through batuation activities by giving examples to children. Fourth, the habit of saying the word ”Excuse me” is done by giving understanding to children.